CASH algorithm versus 3‐point checklist and its modified version in evaluation of melanocytic pigmented skin lesions: The 4‐point checklist. Issue 6 (21st November 2015) - di Meo, Nicola; Stinco, Giuseppe; Bonin, Serena; Gatti, Alessandro; Trevisini, Sara; Damiani, Giovanni; Vichi, Silvia; Trevisan, Giusto
Abstract: Dermoscopy, in expert hands, increases accuracy, sensitivity and specificity in diagnosis of pigmented skin lesions of a single operator, compared with clinical examination. Simplified algorithmic methods have been developed to help less expert dermoscopists in diagnosis of melanocytic lesions. This study included 125 melanocytic skin lesions divided into melanocytic nevi, dysplastic nevi and thin melanomas (<1 mm). We compared the 3‐point checklist and CASH algorithm to analyze different pigmented skin lesions. Based on preliminary results, we proposed a new modified algorithm, called the 4‐point checklist, whose accuracy is similar to the CASH algorithm and whose simplicity is similar to the 3‐point checklist.